ANTIBACTERIAL ACTIVITY OF SOME LACTIC ACID BACTERIA ISOLATED FROM A LOCAL FERMENTED MILK PRODUCT (PENDIDAM) IN NGAOUNDERE, CAMEROON - A. Mbawala; P. Y. Mahbou; H. T. Mouafo; L. N. Tatsadjieu (Journal of Animal and Plant Sciences, 2013)
Fermented milk products are known to have potential activity against gastro-intestinal infections, food-borne pathogens and food-borne spoilage micro-organisms. The objectives of this study were to isolate lactic acid bacteria (LAB) as ferments present in pendidam (a locally fermented milk product), evaluate the antibacterial activity of the isolates against Escherichia coli and Staphylococcus aureus and partially characterise substances of the cell-free supernatant responsible for antibacterial activity. Twenty (20) strains of lactic acid bacteria (LAB) were isolated from 3 of 5 samples of pendidam collected from the locality of Wakwa (Ngaoundere), were identified based on their morphological, physiological and biochemical characteristics and were screened for their antibacterial activity using the well diffusion method on agar medium. A total of 16 Lactobacillus spp. and 4 Streptococcus species were identified. All the lactic acid bacteria (LAB) strains were active against Staphylococcus aureus whereas 6 of them were not active against Escherichia coli. The most active strains against both pathogens were L18 for E. coli and L19 for S. aureus, all belonging to Lactobacillus species and having a maximum inhibition zone of (4.5±0.1) mm. The inhibitory effect of neutralised cellfree supernatants of 10 isolates and thermal sensitivity of the supernatants of five active strains were studied. The results obtained did not show the complete loss of antibacterial activity of the extracts. This is an indication that the tested lactic acid bacterial strains secreted substances responsible for the antagonistic action observed on the pathogens and which will be further identified. This preliminarily work shows the potential application of autochthonous lactic acid bacteria or related substances to improve foods preservation.
Keywords: Fermented milk; lactic acid bacteria; antibacterial activity; Staphylococcus aureus; Escherichia coli